Job Satisfaction and Burnout among Greek Teachers and Physical Education Teachers. A Comparison in Minority and Public Sector Schools in Thrace - Sotirios Vousiopoulos; Olga Kouli; Thomas Kourtessis; Efstratia Tsitskari; Dimos Tsitskari (Annals of Applied Sport Science, 2019)
Background. Job satisfaction has been an issue of intense study interest during the last decades. It could be defined a positive emotional state resulting from the appraisal of one’s job situation and is linked to the characteristics and demands of one’s work. Also that interest in the concept of job burnout has grown rapidly and the knowledge of burnout has increased considerably. Burnout is defined as a negative experience that is a reaction of people to jobrelated stress. Objectives. The present study seeks to investigate the levels of job satisfaction and burnout in Teachers and Physical Education Teachers of Minority and Public Sector Schools, as well as their relation to demographic characteristics. Methods. The Employee Satisfaction Inventory questionnaire, adapted for the Greek population, was employed to assess job satisfaction. For the measurement of burnout, Maslach Burnout Inventory questionnaire was used, which has also been validated for the Greek population. Questionnaires were picked up by 297 Primary School Teachers and by 142 Physical Education Teachers, who serve at 186 Minority Schools and 253 Public Schools of Thrace. Results. The results of the study revealed a negative relation between job satisfaction and burnout; teachers experience relatively moderate burnout levels, their job satisfaction level is high. The results showed that Physical Education teachers experience higher job satisfaction and lower burnout than Primary school teachers. Finally, concerning school, the type of school affects satisfaction in relation to the factor “job conditions”. Conclusion. For the first time, burnout and job satisfaction of teachers in minority schools was studied and the results revealed that when job satisfaction increases, the perceived burnout decreases, where job satisfaction and burnout presented medium to high negative correlation.